National palliative care capacities around the world: Results from the World Health Organization Noncommunicable Disease Country Capacity Survey. (January 2018) - Sharkey, Lee; Loring, Belinda; Cowan, Melanie; Riley, Leanne; Krakauer, Eric L
Background: Previous estimates of global palliative care development have not been based on official country data. Aim: The World Health Organization Noncommunicable Disease Country Capacity Survey of World Health Organization member state officials monitors countries' capacities for the prevention and control of noncommunicable diseases. In 2015, for the first time, questions were included on a number of palliative care development metrics to generate baseline data for monitoring global palliative care development. Design: Participants were given instructions, a glossary of terms, and 3 months to complete this closed, non-randomized, online survey. Questions were developed through a consultative process with relevant technical World Health Organization departments. Setting/participants: Health ministry officials serving as noncommunicable disease focal points from 177 out of 194 (91%) of World Health Organization Member States completed the voluntary survey. Results: This survey reveals that (a) a minority (37%) of countries have an operational national policy for noncommunicable diseases that includes palliative care, (b) palliative care is least likely to have funding available compared with other core noncommunicable disease services, and (c) there is a large country-income gradient for palliative care funding, oral morphine availability, and integration of palliative care services at the primary levels of the health system. Conclusion: Palliative care for noncommunicable disease patients must be strengthened in a majority of countries. These data provide a baseline for trend measurement of official country-level and global palliative care development. A repeat assessment is taking place in the first half of 2017.